Assessing distributed leadership for learning and teaching quality: a multi-institutional study. Issue 2 (4th March 2017) - Carbone, Angela; Evans, Julia; Ross, Bella; Drew, Steve; Phelan, Liam; Lindsay, Katherine; Cottman, Caroline; Stoney, Susan; Ye, Jing
ABSTRACT: Distributed leadership has been explored internationally as a leadership model that will promote and advance excellence in learning and teaching in higher education. This paper presents an assessment of how effectively distributed leadership was enabled at five Australian institutions implementing a collaborative teaching quality development scheme called the Peer Assisted Teaching Scheme. The Scheme brings together expertise from teams of academics, coordinators, and institutional learning and teaching portfolio holders to the shared goal of enhancing learning and teaching quality. A distributed leadership benchmarking tool was used to assess the Scheme's effectiveness, and we found that (i) the Scheme is highly consistent with the distributed leadership benchmarks, and that (ii) the benchmarking tool is easily used in assessing the alignment (or otherwise) of teaching and learning quality initiatives with distributed leadership benchmarks. This paper will be of interest to those seeking to assess implementations of distributed leadership to improve teaching quality and leadership capacity.